The Dynamics of Information Asymmetry in Corporate Financial Decision- Making in the Digital Era - Rika Solihah (Jurnal Ragam Pengabdian, 2026)
Information asymmetry has long been recognized as a fundamental issue in corporate finance, influencing investment, financing, and dividend decisions. In the digital era, rapid technological advancement has transformed the nature of information dissemination, creating both opportunities and new challenges for transparency and market efficiency. This study aims to analyze the dynamics of information asymmetry in corporate financial decision-making within the context of digital transformation. Using a qualitative approach with a literature study design, the research synthesizes classical and contemporary theories of information asymmetry, corporate governance, and digital finance. Data were collected from peer-reviewed journals, academic books, and reports published by reputable international institutions such as the OECD, World Bank, and IMF. The analysis reveals that information asymmetry is shaped by the interaction of financial reporting quality, governance mechanisms, regulatory environments, and digital technologies. Digital governance, blockchain-based reporting, and enhanced ESG disclosure play a significant role in reducing information gaps, although they may also generate new forms of algorithmic asymmetry. Overall, the findings indicate that effective integration of digital technology and strong corporate governance can mitigate information asymmetry and improve the efficiency of corporate financial decisions in the digital era.